2021
DOI: 10.3390/pathogens10111368
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Ecosystem-Based Approach to Shed Light on the Heterogeneity of the Contamination Pattern of Listeria monocytogenes on Conveyor Belt Surfaces in a Swine Slaughterhouse in the Province of Quebec, Canada

Abstract: The role of the accompanying microbiota in the presence of Listeria monocytogenes on meat processing surfaces is not yet understood, especially in industrial production conditions. In this study, 300 conveyor belt samples from the cutting room of a swine slaughterhouse were collected during production. The samples were subjected to the detection of L. monocytogenes. Recovered strains were characterized by serogrouping-PCR, InlA Sanger sequencing and for their ability to form biofilm. A selection of isolates wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…It should be noted that this study is part of a larger project which was developed in two phases. The first phase aimed to evaluate spatial and temporal Listeria monocytogenes contamination on the six production lines in a swine slaughterhouse cutting room in Quebec, Canada and to identify microbial determinants of the presence or absence of the bacteria on those surfaces [ 28 ]. The current study is the second phase of that project and aims to evaluate the microbiota’s homogeneity on contact surfaces according to processing line (each line is dedicated to a specific cut of meat) and according to different visits using the samples harvested during the first phase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that this study is part of a larger project which was developed in two phases. The first phase aimed to evaluate spatial and temporal Listeria monocytogenes contamination on the six production lines in a swine slaughterhouse cutting room in Quebec, Canada and to identify microbial determinants of the presence or absence of the bacteria on those surfaces [ 28 ]. The current study is the second phase of that project and aims to evaluate the microbiota’s homogeneity on contact surfaces according to processing line (each line is dedicated to a specific cut of meat) and according to different visits using the samples harvested during the first phase.…”
Section: Methodsmentioning
confidence: 99%
“…The current study is the second phase of that project and aims to evaluate the microbiota’s homogeneity on contact surfaces according to processing line (each line is dedicated to a specific cut of meat) and according to different visits using the samples harvested during the first phase. The sampling procedures as well as the processing of the microbiota samples have been described in detail in the work of Shedleur-Bourguignon et al, 2021 [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of L. monocytogenes growth could also be the result of bacteriocin secretion by other species, such as Enterococcus faecium [ 18 ]. Other studies, in contrast, demonstrated positive interactions between L. monocytogenes and other bacterial genera [ 19 , 20 ]. Indeed, for example, Flavobacterium spp., which was part of the background microbiota of a seafood processing plant, was reported to enhance the colonization of L. monocytogenes on stainless steel surfaces [ 19 ].…”
Section: Introductionmentioning
confidence: 91%